2014
DOI: 10.1111/jgh.12584
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin activates the renin–angiotensin system to ameliorate the pathophysiology of severe acute pancreatitis

Abstract: This study shows that ulinastatin has differential effects on the two axes of the RAS during SAP. Our results further suggest that upregulation of components of the ACE2-Ang-(1-7)-Mas pathway might be an important mechanism contributing to the therapeutic role of ulinastatin in alleviating pancreatitis-associated symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…These data, together with a previous study (27), demonstrated that exogenous Ang-(1-7) may affect the balance of Ang-(1-7)/Ang II in addition to ACE2/ACE in AP. This is also consistent with previous animal experiments; that identified that ulinastatin significantly ameliorated pancreatic pathology through upregulating ACE2 and Ang (1-7) in addition to the serum biochemistry indicators of CAE-induced SAP mice (28). The re-establishment of the balance of RAS through upregulating Ang-(1-7) and ACE2 expression, which can ameliorate apoptosis, may possess clinical therapeutic potential.…”
Section: Discussionsupporting
confidence: 92%
“…These data, together with a previous study (27), demonstrated that exogenous Ang-(1-7) may affect the balance of Ang-(1-7)/Ang II in addition to ACE2/ACE in AP. This is also consistent with previous animal experiments; that identified that ulinastatin significantly ameliorated pancreatic pathology through upregulating ACE2 and Ang (1-7) in addition to the serum biochemistry indicators of CAE-induced SAP mice (28). The re-establishment of the balance of RAS through upregulating Ang-(1-7) and ACE2 expression, which can ameliorate apoptosis, may possess clinical therapeutic potential.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, serum IL-10 was reduced 24h and on 4 th day after AP induction in the AP group as compared with control group. This was in accordance with Liu et al, 2014 [38] who found decrease in serum IL-10 in ceruleininduced SAP mice. IL-10 is anti-inflammatory cytokine that correlates with the severity of pancreatitis.…”
Section: Discussionsupporting
confidence: 93%
“…Oruc et al (25) demonstrated that the activation of the RAS is closely associated with AP. In addition, previous studies conducted by the present research group have shown that SAP is associated with upregulation of the ACE2-Ang-(1-7)-Mas axis and promotes increased circulating levels of Ang-(1-7) (26)(27)(28). however, whether the ACE2-Ang-(1-7)-Mas axis serves a protective role in the pathogenesis of pancreatitis, and the signaling pathway through which the ACE2-Ang-(1-7)-Mas axis protects pancreatic cells from inflammation remain unknown.…”
Section: Introductionsupporting
confidence: 56%